2010
DOI: 10.1371/journal.pone.0010337
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Alteration of Gene Regulatory Networks through MicroRNAs of the HIV-Infected Brain: Novel Analysis of Retrospective Cases

Abstract: HIV infection disturbs the central nervous system (CNS) through inflammation and glial activation. Evidence suggests roles for microRNA (miRNA) in host defense and neuronal homeostasis, though little is known about miRNAs' role in HIV CNS infection. MiRNAs are non-coding RNAs that regulate gene translation through post-transcriptional mechanisms. Messenger-RNA profiling alone is insufficient to elucidate the dynamic dance of molecular expression of the genome. We sought to clarify RNA alterations in the fronta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…Additional factors that may require attention include HAART resistance mutations, the particular mutational profile of the peripheral and CSF viruses that may influence HIV-1 neurovirulence, epigenetic mechanisms, and micro-(mi-) RNA expression. Factors including elevated plasma lipo-polysaccharide (LPS) as well as co-infections including HCV may be important in groups such as injection drug and alcohol abusers [9196]. …”
Section: Molecularmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional factors that may require attention include HAART resistance mutations, the particular mutational profile of the peripheral and CSF viruses that may influence HIV-1 neurovirulence, epigenetic mechanisms, and micro-(mi-) RNA expression. Factors including elevated plasma lipo-polysaccharide (LPS) as well as co-infections including HCV may be important in groups such as injection drug and alcohol abusers [9196]. …”
Section: Molecularmentioning
confidence: 99%
“…In human astrocyte cultures, activation of indoleamine-2,3-dioxygenase (IDO) results in elevation of tryptophan catabolism and the production of neurotoxins including kynurenine due to Tat protein for HIV-1B and not C. The authors conclude from the latter experiment that the prevalence of HAD may correlate with epidemiological differences in HIV-1B vs. C [139,145148]. Finally, microarray technology has been applied to NeuroAIDS to measure simultaneous expression of large numbers of genes including recently discovered micro-(mi)-RNAs, as reviewed in detail elsewhere (Table 3) [49,50,96,136,138,140,141,145154]. …”
Section: Molecularmentioning
confidence: 99%
“…Within mammalian cells, miRNAs associate with the RNA-induced silencing complex to hybridize 8-mer ''seed'' sequences in the 3'-untranslated regions of target mRNAs (Tatro et al, 2010). These regions are partially complementary to miRNAs that are directed for degradation and/or suppressed translation (Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Both miR-125a and miR-22 were found to be upregulated in HIV or HIV/major depressive disorder (MDD, Tatro et al 2010). Induction of these dysregulated miRNAs leads to decreased protein translation of interferon-induced transmembrane protein 3 (IFITM3), an intracellular membrane protein, and soluble tumor necrosis factor receptor (sTNFR1A), a secreted protein in primary human neuronal cultures.…”
Section: Introductionmentioning
confidence: 99%
“…IFITM protein is shown to inhibit HIV replication (Lu et al 2011), and sTNFR1A is involved in neuroinflammation. miR219, which was shown to modulate NMDA receptor-mediated neurobehavioral dysfunction in schizophrenia (Kocerha et al 2009), is also shown to be upregulated in HIV/MDD (Tatro et al 2010). …”
Section: Introductionmentioning
confidence: 99%